Selected Heavy Metal (Zn, Pb and Cd) Pollution in Soil and Water from Marakwet East and Marakwet West, Elgeyo Marakwet County, Kenya - Chepkorir, L.; Kituyi , L.; Lutta, S. (Africa Environmental Review Journal, 2022)
Heavy metal pollution has become a global public health issue, aggravated by human activities in the world leading to food and drinking water quality challenges. The present study aimed at assessing selected heavy metal (Zn, Pb and Cd) pollution in soil and water from Marakwet East and Marakwet West, Elgeyo Marakwet County, Kenya. The sampling sites namely the Chepkaitit, Moiben, Embobut, Arror, Mon, and Mosongu Rivers, were purposively selected. Water samples were collected from three sites of each River during rainy and dry season. Three composites consisting of three subsets of soils were also collected from the Marakwet East and Marakwet West during the rainy and dry seasons. The soil samples came from the same areas as the water samples. Collected samples were transported to the University of Eldoret laboratory where analysis was done using Atomic Absorption Spectrophotometry (AAS). Data was analysed using Analysis of Variance and Correlation analysis and results were presented using graphs, figures and distribution tables. In water samples, Zn concentrations were higher during wet season than dry season (p>0.05). Zn levels in water samples increased significantly from 0.212 ppm upstream to 0.225 ppm midstream. There was significant increase in Cd levels from 0.066 ppm upstream to 0.068 ppm midstream. Soil samples collected during wet season from R. Chepkaitit recorded Cd levels of 0.071, 0.078 and 0.053 ppm at upstream, midstream and downstream respectively. Similarly, Pb levels increased from 0.470 ppm to 0.720 ppm to 0.791 ppm in water samples collected from upstream, midstream and downstream of R. Mon respectively. The concentration of pb and Cd in some water and soil samples exceeded the WHO standards. The study recommends that the health personnel from the ministry of Agriculture and health from Elgeyo Marakwet County should train and screen the local residents on the sources and health effects of heavy metals poisoning.